Implementing Bloom’s Revised Taxonomy in Analyzing the Reading Comprehension Questions - Ekalia, Yulian Juita; Selamat, Ely Heldydiana; Jemadi , Fransiskus; Jelimun, Maria Olga; Setiawan, Anjelus A. (English Education:Journal of English Teaching and Research, 2022)
Bloom's revised taxonomy is the most frequently utilized as an instrument for objective-as a basis for assessment and as a representation for producing objects that evaluate processes ranging from memorization to more complex cognitive levels such as knowledge assessment. It is predicted that the mix of cognitive levels in the 2013 curriculum will drive students to think critically, to think creatively, to be problem solvers, and have a decision maker competencies. Using teaching resources such as textbooks as one of the learning media to train students' critical thinking. The goal of this research is to figure out the cognitive levels in the revised Blooms' Taxonomy utilized in The Ministry of Education and Culture's (MOEC) textbook "Bahasa Inggris SMA/MA/SMK,MAK grade X." The qualitative approach and content analysis were used in this study's research design. This study analyzed the proportion of the lower-order thinking (LOT) and the higher-order thinking skills (HOTS) questions based on the cognitive levels Bloom’s taxonomy. The researcher compiled a list of the reading comprehension questions and counted degree of cognition in each book chapter. According to the findings, there are 114 reading comprehension questions. Lower order thinking (LOT) is the most prominent level in this book. Lower-order thinking skills (LOTS) account for 69 percent of the total, whereas higher-order thinking skills (HOTS) account for only 8%. It was suggested that the material of the textbook be expanded upon, with a greater emphasis on Higher Order Thinking Questions. Keywords:Reading Comprehension, Questions, Bloom’s Taxonomy